The TaMYB55–TaSnRK1α1–TabZIP9 module confers heat stress tolerance in wheat - Wen Yang; Renhan Li; Man Feng; Zhe Chen; Weiwei Guo; Yumei Zhang; Huiru Peng; Yingyin Yao; Zhaorong Hu; Feng Qin; Ive De Smet; Mingyi Bai; et al. (Proceedings of the National Academy of Sciences, 2026)
Heat stress poses a severe threat to global crop yields and food security. Here, we demonstrate that TaSnRK1α1, the α-catalytic subunit of sucrose non-fermenting-1-related kinase 1, serves as a pivotal regulator that confers thermotolerance and enhances grain weight in wheat ( Triticum aestivum L.). The findings reveal that TaMYB55 directly binds to the TaSnRK1α1 promoter to activate its expression, which positively contributes to heat tolerance in wheat. An A-to-G substitution in the TaSnRK1α1 promoter enhances the binding affinity of TaMYB55, which cosegregates with wheat thermotolerant phenotypes. In addition, we show that TaSnRK1α1 interacts with and phosphorylates the transcription factor TabZIP9, which subsequently promotes TabZIP9 degradation. Genetic analyses confirm that TaSnRK1α1 functions upstream of TabZIP9, and loss or gain-of-function of TabZIP9 significantly alters thermotolerance in wheat by modulating reactive oxygen species homeostasis and scavenging capacity. Together, our findings shed light on the importance of the TaMYB55–TaSnRK1α1–TabZIP9 signaling module in the regulation of heat tolerance, providing practical strategies for engineering climate-tolerant crops.